What are the virtual reality solutions for dual-task intervention to promote health in aging? A scoping review - Bruni, Francesca; Bigotto, Francesco; Mancuso, Valentina; Cavedoni, Silvia; Panigada, Jonathan; Stramba-Badiale, Marco; Serino, Silvia; Pedroli, Elisa (Frontiers in Human Neuroscience, 2026)
IntroductionCognitive-motor dual-task (CMDT) performance is crucial for everyday activities, particularly in older adults who commonly experience deficiencies in cognitive and motor domains. These impairments compromise daily functioning, causing a decrease in quality of life. However, traditional assessment and training methods face significant limitations. Conventional protocols often exhibit limited ecological validity, as they fail to replicate real-world performance demands adequately. Moreover, they are characterized by substantial methodological heterogeneity and offer restricted capacity for real-time performance monitoring and the delivery of personalized feedback. Virtual Reality (VR) offers a promising approach by creating controlled, real-life environments that enable precise assessment and personalized training. However, VR-based CMDT remains largely unexplored. This review evaluates current VR solutions for CMDT, examining assessment, and intervention designs.MethodsA scoping review was conducted on April 17, 2023 (and updated on January 21, 2025), following the PRISMA for Scoping Review guidelines, on three databases: Web of Science, Embase, and PubMed. We included original articles, based on the following criteria: English-language; original research articles reporting empirical data from experimental, quasi-experimental, or observational studies; articles employing CMDT assessment or training; use of VR-based applications during a CMDT; older population participants (≥65 years). Reviews, meta-analyses, editorials, conceptual articles, case studies, and short papers were excluded.ResultsOf 2,649 papers, 21 studies met the inclusion criteria: 17 assessment and four training studies. Research focused on healthy older adults and individuals with early cognitive decline, sensory deficits, and those at fall risk. Assessment studies mainly employed immersive and semi-immersive systems simulating realistic scenarios in virtual environments, primarily using “walking while” paradigms with cognitive tasks. Training studies frequently utilized non-immersive or semi-immersive solutions with less naturalistic environments, demonstrating improvements in gait parameters, dual-task performance, motor functions, and cognitive abilities. Substantial methodological heterogeneity was observed in intervention duration, frequency, and DT cost calculations, with limited attention to user experience evaluation.DiscussionVR-based CMDT applications show promise for assessment and intervention in aging. However, significant gaps exist regarding the lack of standardized methodological approaches, ecological validity, and user-centered design considerations. Future research should address these limitations to enhance the accessibility and effectiveness of VR-based CMDT interventions.